COMPARATIVE STUDY OF HERBAL AND CONVENTIONAL ANTIHISTAMINES IN THE MANAGEMENT OF ALLERGIC RHINITIS IN CHILDREN (Journal of Medical & Health Sciences Review, 2025)
Background:Allergic rhinitis (AR) is a common chronic condition in children that significantly impacts quality of life and is typically managed using antihistamines, both conventional and herbal.Objective:To compare the efficacy and safety of herbal versus conventional antihistamines in the management of AR in children.Methodology:A prospective, descriptive, comparative observational study was conducted at the University of Lahore in collaboration with the Pediatric Outpatient Department of Mayo Hospital, Lahore, over 12 months (April 2022–March 2023). A total of 130 children aged 6–12 years clinically diagnosed with AR were enrolled and divided into two groups: herbal antihistamine group (n=65) receiving Nigella sativa and Perilla frutescens, and conventional antihistamine group (n=65) receiving cetirizine or loratadine. Efficacy was assessed using the Total Nasal Symptom Score (TNSS) at baseline, weeks 2, 4, 8, and 12, along with adverse effects, recurrence rates, and parental satisfaction.Results:Both groups showed significant symptom reduction over 12 weeks (p